E-Invoicing: Digital Transformation for Operational Efficiency - Sutisna, Entis; Suhendra, Elwin; Purnama, Diki Gita (Journal of Business and Economics Research (JBE), 2024)
This research aims to identify the benefits of E-Invoicing in improve operational efficiency and explore the challenges faced in implementation process. By understanding its aspects, it is hoped that the company be better prepared to adopt E-Invoicing and gain benefits from the transformation digital it offers. The data analysis method used in this research is the descriptive method quantitative and qualitative. A combination of quantitative and qualitative approaches is possible us to gain a comprehensive understanding of the impact of E-invoicing on operational efficiency. this research design uses a survey (questionnaire) and direct interviews. The result of analysis by SPSS 16 found that the benefit of E-Invoice has sig.Levene’s Test for Equity of Variance is > 0.05 which mean the data between group A is homogeneous or same. Based on the interview with the user of E-Invoicing, the respondent inform that the method of E-Invoicing has a good impact for providing the benefit, experiences, faster of processing and more efficient because its no longer use paper anymore instead of organize by system. The research found that the analysis were match among analysis by SPSS 16 and interview the respondent, it’s found that the respondents agree by applying the E-invoicing deeply give a benefit and increase the productivity in order impact the operational efficieny.